Hepatitis C Virus (HCV): Prevalence in a Gynecological Urgent Care Clinic Population - J. Adusumalli; E. A. Bonney; L. Odenat; D. J. Jamieson (Hindawi Limited, 2004)
Objective: To determine the prevalence of hepatitis C virus (HCV) among women seeking urgent gynecological care.